2020
DOI: 10.1111/1541-4337.12542
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of byproducts from tropical fruits: Extraction methodologies, applications, environmental, and economic assessment: A review (Part 1: General overview of the byproducts, traditional biorefinery practices, and possible applications)

Abstract: Tropical fruits represent one of the most important crops in the world. The continuously growing global market for the main tropical fruits is currently estimated at 84 million tons, of which approximately half is lost or wasted throughout the whole processing chain. Developing novel processes for the conversion of these byproducts into value‐added products could provide a viable way to manage this waste problem, aiming at the same time to create a sustainable economic growth within a bio‐economy perspective. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 351 publications
(294 reference statements)
0
47
0
1
Order By: Relevance
“…Seeds of fruit tree species often represent an important by-product of juice/jam food industries, as well as a relevant source of phytochemicals [72]. This is the case of limonoids in Citrus species [73], and of secoiridoids in Olea species [74].…”
Section: Fruit Tree Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds of fruit tree species often represent an important by-product of juice/jam food industries, as well as a relevant source of phytochemicals [72]. This is the case of limonoids in Citrus species [73], and of secoiridoids in Olea species [74].…”
Section: Fruit Tree Speciesmentioning
confidence: 99%
“…This is the case of limonoids in Citrus species [73], and of secoiridoids in Olea species [74]. In the last decade, many utilizations were proposed to add value to these agricultural by-products, including the possibility to use them for nutritional purposes [72,75]. The direct consumption of seeds is not possible in many cases, since they are coriaceous, and/or bitter and astringent.…”
Section: Fruit Tree Speciesmentioning
confidence: 99%
“…However, the use of camu‐camu seeds is virtually nonexistent. Considering the amount of seeds generated in South America and their bioactivity, it is possible to incentivize their industrial processing, thus, avoiding losses and contributing to the circular economy engagement in the fruit processing sector (Dzah, Duan, Zhang, Boateng, & Ma, 2020; Fidelis et al., 2019; Villacís‐Chiriboga, van Camp, Vera, & Ruales, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, variation in concentration of metabolites in different fruit parts is highly dependent on varieties, environment, and management practices, [10] though previous studies suggested that concentration of metabolites is higher in discarded fractions with marked differences than edible parts. [35] Peel and seed are considered to hold a higher concentration of metabolites than the pulp with a considerable fraction of phenolic compounds, polysaccharides, and tyrosinase inhibitors. [10,34] Longan seed extract has the highest level of phenolic compounds compared to dried flesh.…”
Section: Introductionmentioning
confidence: 99%